A new record of the subfamily Isometopinae (Heteroptera: Miridae) from the Korean Peninsula - Jung, Sunghoon; Duwal, Ram K.; Lee, Seunghwan (Zootaxa, 2015)
The subfamily Isometopinae (Heteroptera: Miridae) is recognized for the first time in the Korean Peninsula based on a single female specimen, Isometopus amurensis Kerzhner. Herein, diagnosis of a female specimen, illustration of female genitalia, and habitus figures with biological notes are provided.